The SFT2D2 gene is associated with the autoimmune pathology of schizophrenia in a Chinese population - Liu, Duilin; Wu, Lin; Wei, Hui; Zhu, Caiyun; Tian, Runhui; Zhu, Wanwan; Xu, Qi (Frontiers in Neurology, 2022)
The relative risk of GWAS-confirmed loci strongly associated with schizophrenia may be underestimated due to the decay of linkage disequilibrium between index SNPs and causal variants. Here, we re-genotyped three schizophrenia-associated SNPs (rs10489202, rs11586522 and rs6670165) confirmed by GWAS in total of 9801 case-control subjects of Chinese Han origin and identified a rare variant (rs532193193) in the SFT2D2 locus that was strongly associated with schizophrenia. An in-house enzyme-linked immunosorbent assay (ELISA) was developed to determine circulating IgG antibodies against peptide antigens encoded by SFT2D2 gene in 332 schizophrenia patients and 350 healthy subjects. Compared with control subjects, patients with schizophrenia showed increased IgG levels. Receiver operating characteristic (ROC) analysis revealed an area under the ROC curve (AUC) of 0.803 with sensitivity of 28.57 % against specificity of 95 % for the anti-SFT2D2 IgG assay. Our findings indicate that SFT2D2 is a novel gene for risk of schizophrenia, while endogenous anti-SFT2D2 IgG may underlie the pathophysiology of the immunological aspects of schizophrenia.